Lactancia Materna: Beneficios para los bebés, las madres, y la sociedad: FCS8726-Span/FY458, rev. 8/2009 - Peñuela, Claudia; Hillan, Jennifer (EDIS, 2009)
Revised! FCS8726-Span, a 2-page fact sheet by Claudia Peñuela and Jennifer Hillan, is the Spanish language version of FCS8726/FY457 Breastfeeding: Benefits for Babies, Mothers and Society. It lists the benefits of breastfeeding for babies, mothers, and society. Includes tips for breastfeeding and references. Published by the UF Department of Family Youth and Community Sciences, August 2009.